Dogs on Duty - O'Neill, Catherine; Nang ChanYeema (Washington, D.C, USA The National Geographical Society, 1988)
Describes the ways in which dogs are bred and trained for such careers as livestock guardian, herder, helper for the disabled, sled-puller, and entertainer.
Keywords: Adult Nonfiction